European Research Libraries and Special Collections - Jefcoate, Graham (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2007)
An interesting, and perhaps rather unexpected, aspect of current thinking on the future of research libraries has been a new emphasis placed on the role of rare books and special collections. As the delivery of traditional library services, for example collection building and description, becomes more dependent on national or regional consortia, so libraries are considering what will remain to be done at the local and institutional level. Various library “trend watchers” have suggested local activities on which individual libraries may wish to concentrate in the future, including information literacy, customised user support in information retrieval, and so on. A surprising number have also mentioned “legacy” collections of printed material and other special collections as a likely focus of future professional efforts at the local library level.